Microbial inoculum selection for product composition tuning in methane-arrested anaerobic leach bed reactors - Poblete-Castro, I (ELSEVIER SCI LTD, 2025)
The production of short-chain fatty acids, commonly referred to as volatile fatty acids (VFA), from food waste through methane-arrested anaerobic digestion (MAAD) is a promising strategy for valorizing organic residues. However, the influence of microbial inoculum selection on VFA yield and composition is not yet fully elucidated. In this study, we investigated VFA, lactic acid, and ethanol production in leach bed reactors (LBR) operated with and without pH control for three different inocula: two acclimated acidogenic consortia at various pH levels (4 and 7) and one thermally treated methanogenic inoculum. Results showed that neutral pH operation favored hydrolysis and acidification, regardless of the inoculum type, but also led to ethanol co-production, representing up to 56 % of the soluble chemical oxygen demand. Conversely, the use of an acclimated inoculum without pH control suppressed ethanol formation entirely, achieving the highest selectivity towards short-chain acids synthesis despite reduced hydrolytic capacity. Microbial community analysis revealed that inoculum type and pH regime strongly shaped the reactor microbiota, influencing fermentation pathways. Acclimated inocula preserved metabolic behaviors from their source reactors, demonstrating the potential of microbial conditioning to modulate fermentation outputs. These findings emphasize the importance of inoculum selection as a strategic tool to steer product distribution in MAAD systems and support the development of tailored bioprocesses for circular bioeconomy applications.